"Everything has been done at some time or another..." An Interview with Ernest Hilgard. Issue 3 (11th January 2022) - Cardeña, Etzel
ABSTRACT: Ernest R. Hilgard is not only one of the most important hypnosis theoreticians and researchers in history, but one the most eminent psychologists of the 20 th century. This paper starts with a brief summary of his contributions to hypnosis, emphasizing his dissociation theory, and placing it within previous and later dissociation theories of hypnosis. I then transcribe an interview with him circa 1989, which I recorded with his authorization for later use, emphasizing dissociation in hypnosis. He also reminisced about historical figures in psychology.